Islamic Education Policy in the Era of Digital Transformation: Challenges and Future Directions - Refnil Yetti; Samsu Samsu; Mahmud Mahmud (Ahlussunnah: Journal of Islamic Education, 2026)
Digital Revolution 4.0 has driven fundamental changes across various sectors, including Islamic education, thereby requiring policies that are adaptive to technological advancements and the demands of twenty-first-century competencies. This article aims to analyze the directions of Islamic education policy in Indonesia and identify the challenges encountered in its implementation in the digital era. The study employs a qualitative method using a content analysis approach. Data were collected from Islamic education policy documents, including the Islamic Education Roadmap 2020–2035, relevant regulations, and related academic literature. The data were analyzed through coding, categorization, and thematic interpretation to uncover policy orientations and implementation challenges. The findings reveal that Islamic education policies in Indonesia have directed transformation in five key areas: curriculum development, learning innovation, institutional governance strengthening, human resource capacity enhancement, and the reinforcement of educational regulations and funding. Nevertheless, policy implementation continues to face several challenges, including regional digital disparities, inadequate digital competencies among educators, limited technological infrastructure, curriculum misalignment with twenty-first-century competency requirements, the threat of digital radicalism, adaptation challenges faced by traditional Islamic educational institutions, and tensions between national standardization and the need for local contextualization. These findings indicate that the digital transformation of Islamic education requires an integrative, adaptive, and sustainable policy approach. This article contributes to the advancement of Islamic education policy studies by proposing an analytical framework for understanding the developmental directions and implementation challenges of Islamic education policies in response to the digital era.